Eschatologie et discours sur la fin des temps dans la péninsule Ibérique (viiie-xie siècle) - Bosseman, Gaelle (Bibliothèque de la Casa de Velázquez, 2023)
Eschatology and discourses on the end of time are an important subject in medieval literature. In the Iberian Peninsula, the study of Beatus de Liébana has given rise to debates on the existence of apocalyptic fears linked to the approach of the year 800 or the year 1000, or following the Muslim conquest. This book aims to better integrate the Iberian situation into a broader panorama, and to highlight the scholarly character and diversity of a textual and iconographic production with multiple functions, which approaches the end of time from a perspective devoid of any apocalyptic urgency.